Metode Pavement Condition Index Perkerasan Rigid Pavement Jalan Raya Bandar Buat Kota Padang STA 02+000 - STA 07+000 - Prayitno, Eko; Veronika, Veronika; Yusri, Nori; Fuadi, Al Busyra (Universitas Batanghari Jambi, 2025)
The city highway for the city of Padang is a traffic route in West Sumatra province that is mostly passed by motorized vehicles and vehicles with four or more axes. Rigid pavement is a type of pavement that uses concrete as the main material of pavement and is one of the types of road pavement used, in addition to flexible pavement. The purpose of this study is to find out the types of damage that exist on the rigid pavement surface layer and to find out the value of the pavement condition or the level of damage that occurs on the rigid pavement surface on the city highway section for STA 02+000-STA 07+000 and to find out the type of maintenance program that is in accordance with the condition of the road. The methods used are road condition analysis using the pavament condition index (PCI) method, calculating the damage level (density), determining the deduct value of each type of damage, calculating the alowable maximum deduct value (m), determining the total deduct value (TDV), determining the corrected deduct value (CDV) and calculating the PCI (pavament condition index) value. Overall for each segment, the results are: segment 1 STA 02+000-STA 03+000 PCI value = 82.2 (very good), segment 2 STA 03+000-STA 04+000 PCI value = 86.2 (perfect), segment 3 STA 04+000-STA 05+000 PCI value = 82.8 (very good), segment 4 STA 05+000-STA 06+000 PCI value = 79.6 (very good), segment 5 STA 06+000-STA 07+000 PCI value 84.2 (very good). The value of the pavament condition index (PCI) from all segments, then the condition of the city highway for STA 02+000-STA 07+000 with an overall PCI value of 83 (very good) with a routine maintenance program, road cleaning from rock or soil fall, surface patching and crack closure.